The egg and the nucleus: a battle for supremacy - Gurdon, J B (Development (Cambridge), 2013)
Sir John Gurdon and Professor Shinya Yamanaka were the recipients of the 2012 Nobel Prize for Physiology or Medicine. This Spotlight article is a commentary on the early nuclear transplant work in Xenopus, which was very important for the Nobel award in 2012, and the influence of this work on the reprogramming field.